2006
DOI: 10.1016/j.clim.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human T-cell epitopes and highly immunogenic analog peptides on the non-typeable Haemophilus influenzae P6 outer membrane protein

Abstract: P6 outer membrane protein is one of the candidates for a vaccine formulation against non-typeable Haemophilus influenzae (NTHi) infection. However, otitis-prone children who have recurrent episodes of acute otitis media due to NTHi fail to respond adequately to P6. An innovative approach to vaccination is therefore required to augment such children's immune response. To develop an effective peptide vaccine, we established P6-specific CD4(+) T-cell lines (TCLs) restricted by the human histocompatibility leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The immunogenicity of P6 is facilitated by the presence of a CD4 helper T cell epitope [13], [24], [25]. The presentation of the epitope to P6-specific CD4 + T cells is likely enhanced by the presence of the lipid motif on the antigen when endocytosed by the APC upon recognition by TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenicity of P6 is facilitated by the presence of a CD4 helper T cell epitope [13], [24], [25]. The presentation of the epitope to P6-specific CD4 + T cells is likely enhanced by the presence of the lipid motif on the antigen when endocytosed by the APC upon recognition by TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Beck-Sickinger et al (39), the epitopes of P6 were identified and localized within residues 31 to 46 and 59 to 70 and in the C-terminal part of P6, which partly overlapped the predicted T-and B-cell combined epitope P6-61 in our study; however, the lipopeptides containing the sequence pattern QILDAHAA (P6 residues 47 to 54) and the mouse B-cell epitope GEYV (P6 residues 43 to 46) induced high titers of anti-P6 antibodies (39), which were in line with that of P6-61 in the study. Ishida et al (40) established P6-specific CD4 ϩ T-cell lines restricted by the human histocompatibility leukocyte antigen (HLA)-DR9 molecule and revealed a human T-cell epitope on P6 and its core peptide sequence (p77 to 85; EYNIALGQR). Nomura et al (41) studied promiscuous peptides on the nontypeable H. influenzae outer membrane protein P6, identified that human B-cell epitope was located on p71 to 85, which could be recognized by T-cell lines (TCL) in the restriction of HLA-DR9, and induced a proliferative response.…”
Section: Discussionmentioning
confidence: 99%
“…P6 plays a critical role in the structural integrity of the outer membrane as previous work has demonstrated that its absence increases sensitivity of the mutant NTHI strain to a panel of antimicrobial agents (Murphy et al, 2006). Although several studies have evaluated the potential of P6 as a vaccine antigen (Hotomi et al, 1998; Bertot et al, 2004; McMahon et al, 2005; Wu et al, 2005; Ishida et al, 2006; Nomura et al, 2008; Noda et al, 2010), there are no studies detailing its role in the initiation of inflammation during infection in vivo .…”
Section: Introductionmentioning
confidence: 99%